Depression and antidepressant effects of ketamine and its metabolites: The pivotal role of gut microbiota. (1st December 2022) - Hua, Hao; Huang, Chaoli; Liu, Hanyu; Xu, Xiangyang; Xu, Xiangqing; Wu, Zifeng; Liu, Cunming; Wang, Yuanyuan; Yang, Chun
Abstract: The discovery of the robust antidepressant actions of ketamine is regarded as one of the greatest advancements in depression treatment in the past 60 years. Recent findings have provided strong evidence for the presence of bidirectional communication networks between the gastrointestinal tract and the brain in depression. Moreover, increasing evidence supports the antidepressant role of ketamine in regulating the gut microbiome and microbiota-derived molecules; however, the mechanisms underpinning such effects are still ambiguous. This review summarizes the current understanding of the anti-depressant mechanisms of ketamine and its metabolites regarding the bidirectional regulation by microbiota–gut–brain axis. We review the relationship between gut microbiota and the antidepressant mechanisms of ketamine, and discuss the role of stress response, brain-derived neurotrophic factor (BDNF)-mediated neurogenesis, anti-inflammatory effect and neurotransmitters. Highlights: Ketamine and its metabolites exert rapid-acting and sustained antidepressant effects. Gut microbiota contributes to the pathogenesis of depression and the antidepressant actions of ketamine and its metabolites. The relationship between gut microbiota and the antidepressant effects of ketamine and its metabolites is related to stress response, BDNF expression, neurogenesis, anti-inflammatory effect and neurotransmitters.